Oracle & open source - Duncan, Andy (O'Reilly, 2001)
Oracle and Open Source is the first book to tie together the commercial world of Oracle and the free-wheeling world of open source software. As this book reveals, these two worlds are not as far apart as they may seem. Today, there are many excellent and freely available software tools that Oracle developers and database administrators can use, at no cost, to improve their own coding productivity and their system's performance. Moreover, many of the finest Oracle developers are now making their source code freely available so their peers can build upon this code base. Oracle Corporation is even porting its RDBMS to Linux and starting to incorporate a growing number of open source tools in the company's own software. Oracle and Open Source describes close to 100 open source tools you can use for Oracle development and database administration, from large and widely known open source systems (like Linux, Perl, Apache, TCL/Tk and Python) to more Oracle-specific tools (like Orasoft, Orac, OracleTool, and OraSnap). You'll learn how to obtain the software and how to adapt it to best advantage. The book abounds with code examples, download and installation instructions, and helpful usage hints. Not only does it tell you how to find and use existing open source code; Oracle and Open Source gives you the details and the motivation to build your own open source contributions and release them to the Oracle community. You'll learn all about tools like the Oracle Call Interface (OCI) and Perl-DBI (Database Interface), which provide the glue allowing new open source tools to link into commercial Oracle software. With Oracle and Open Source as a guide, you'll discover an enormous number of highly effective open source tools, while getting involved with the thriving community of open source development.